Analisis Penggunaan Rele Diferensial Sebagai Sistem Proteksi Pada Transformator Daya 16 MVA di Gardu Induk Jajar - FITRIANI, NOR RIA; , Umar, S.T., M.T (2017)
Power transformer on the transmission system is a very important main component, and therefore the power transformer must be protected from the faults that can lead to reduce reliability. The fault can be reduced and overcomed by using protection system. A protection system that provides protection againsts electrical equipment in abnormal conditions. One of the devices that use the power transformer protection is differential relay. Differential relays are used as main protection and cannot be used as a backup protection. This relay works by comparing the current of incoming and outgoing flows. Relay will detect fault and instructs circuit breaker (CB) to open (trip). A good protection system is supported by appropriate settings on differential relay protection to prevent fault and improve the reliability of the transmission system. The method used in this research is secondary data by conducting research at Base Camp Surakarta and looking for journal references related to the study. All data is used as a component of mathematical calculations manual. Components that calculated is value ratio current transformer, errors mismatch and parameters at the differential relay in normal conditions. Then, calculating the relay parameter values at the time of fault. The ratio of CT mounted on the transformer in the high voltage side is 75: 1 A and the low voltage side is 800: 1 A. These results are taken with consideration of flow analysis rating that is equal to 67.749 A on the high voltage side and 461.879 A on the low voltage side. Current setting is obtained from the calculation is 0.3 A, and is expected to set the transformer protection system to work optimally.